Karakteristik Morfologi Dan Fisiologi Bakteri Endofit Dan Rizobakteri Dari Tanaman Cengkeh Sehat - Fina Dwimartina; Tri Joko; Triwidodo Arwiyanto (Universitas Wiralodra, 2021)
One of the determining factors in disease control is the use of superior seeds which have good quality and quantity. The use of biological control agents that form a symbiotic mutualism in their host plants can be used as an effort to obtain quality clove seeds. Endophytic bacteria and rhizobacteria have been reported as potential biological control agents for many plant diseases because of their safety in humans and non-target organisms. The purpose of this study was to identify the physiological and morphological characteristics of endophytic and rhizobacterial isolates obtained from clove plants. A total of 46 endophytic bacterial isolates were isolated from healthy clove roots, stems, leaves and flowers. Also, 66 isolates were isolated from the soil around the rhizosphere area. Based on the results of the identification of physiological and morphological characteristics, it is evident that the endophytic and rhizobacterial bacteria tested have the same character as Bacillus spp.